Avaliação das vias aéreas superiores após uso do aparelho Herbst, por meio de sobreposição tridimensional - Palomino-Gómez, Sandra Patricia [UNESP] (2015)
Changes in nasal breathing pattern affect the craniofacial growth. Technological advances, such as Cone beam computed tomography (CBCT), have been used in order to observe three-dimensionally (3D) the skull, face and pharyngeal airway space. The latter, with possible assessment of airway changes induced by orthopedic activators. The aim of this study was to evaluate the changes of the upper airway space resulted from mandibular advancement with Herbst appliance through superposition method of mathematical 3D coordinates. The sample was composed of 24 patients, 10 females and 14 males (16.1 years at the start of treatment - T1) treated for 8 months with Herbst appliance, and compared with a group control composed of 7 females (13.54 yrs at T1). Individuals of the samples were patients with malocclusion Class II division 1, already been through the pubertal growth spurt. The growth sprunt was assessment with hand/wrist radiographs. For each patient, CBCT scans were performed in two stages. The initial phase was conducted by location and identification of 79 anatomical points in the shaft, axial, coronal and sagittal views. Twenty-six anatomical points (skull base, maxilla, vertebra and Hyoid jaw) were adopted for the final analysis using Avizo analysis software®. After calibration of the examiner, each variable was measured three times. The statistical analysis was performed using Levene Test and t-Test with   39   significance level of 5%. The reliability of the measurements showed good reproducibility (ICC ≥ 0.92), exception were the top edge of cervical vertebra 3 and lower border of the Choanae. The results indicated statistical significance in axis Z for PNS (p = 04) compared to control group and for to tip of the epiglottis (p=0.02) compared with control group. Other structures, which were statistically significant, were the left portion of the greater cornu of hyoid...(Complete abstract electronic access below)